2019
DOI: 10.1021/acs.jpcc.9b06685
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nonradiative Energy Transfer between Nitridized Carbon Quantum Dots and Monolayer WS2

Abstract: Two-dimensional (2D) monolayer (1L) transition metal dichalcogenides (TMDs) suffer from low absorption in the visible light region. Nonradiative energy transfer (NRET) is an effective method to enhance such absorption, which, as shown in this study, can be accomplished by using surface nitridized carbon quantum dots (CQDs). The optical absorption and photoluminescence (PL) of CQDs in the visible light region can be greatly enhanced by increasing the level of nitridization. The nitridized CQDs exhibit weak p-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Characterization of CQDs.-The N-CQDs were synthesized according to previous reports with small modification. 34 The product was characterized using different techniques; the results are described below.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of CQDs.-The N-CQDs were synthesized according to previous reports with small modification. 34 The product was characterized using different techniques; the results are described below.…”
Section: Resultsmentioning
confidence: 99%
“…23 By increasing the degree of carbon QDs (CQDs) nitriding, the nonradiative energy transfer efficiency between CQDs and monolayer tungsten disulfide (WS 2 ) would be greatly enhanced 73%. 24 By varying the size of QDs, electron transfer rate between PbS/ CdS QDs and MoS 2 had been tuned. 25 CdSe QDs charge transferred to monolayer WS 2 and improved the PL performance of monolayer WS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cotlet’s group had reported that nonradiative energy transfer rate would be increased from individual CdSe/ZnS QDs to SnS 2 with added number of 2D material layers . By increasing the degree of carbon QDs (CQDs) nitriding, the nonradiative energy transfer efficiency between CQDs and monolayer tungsten disulfide (WS 2 ) would be greatly enhanced 73% . By varying the size of QDs, electron transfer rate between PbS/CdS QDs and MoS 2 had been tuned .…”
Section: Introductionmentioning
confidence: 99%